PERAN WEDDING PHOTOGRAPHY SEBAGAI MEDIA KOMUNIKASI VISUAL DALAM KOMUNITAS HALLUCINATION PHOTO - Rina Astriani; Yeni Nuraeni (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The purpose of this research was to find out the role of photography as a medium of visual communication in wedding photography. The method used qualitative methods by observing and interviewing the founder, chairman and members of the Hallucination Photo community. This study used Kendall Walton's transparency theory. Based on the results of observations and interviews, the researcher concluded that there were many genres in wedding photography. Photography as a visual communication medium in wedding photography has a role in conveying effective and informative meanings or messages through a photo medium by capturing various moments to be immortalized using a tool, namely a camera.